Measurement of carbonization region on leather cutting in CO2 and diode laser-based laser beam process. (June 2022) - Vasanth, S.; Muthuramalingam, T.
There is a quite wide range of animal leathers such as cow leather, sheep leather and buffalo leather used for leather garments and leather goods such as bags, wallets and other customized leather articles. The drawbacks of manual cutting can be eliminated by laser-based cutting. However, unwanted carbonization is happened owing to the higher thermal influence. There is no standard procedure or method available to measure the carbonization region on leather cutting. Diode lasers can process leather rapidly and efficiently. In the present work, an attempt was proposed to introduce the image processing-based measurement approach in leather cutting using CO2 laser and diode laser. The cutting experiments were performed on sheep leather with a thickness of 1 mm. It was found that the proposed can effectively measure the heat-affected zone (HAZ) of leather cutting. It has also been found that diode laser could produce lower HAZ than CO2 laser on leather cutting.